(untitled) (Computer systems and information technologies, 2024)
This paper is aimed at analyzing the contemporary challenges surrounding the integration of generative models API of artificial intelligence (AI) into a unified information system to facilitate automated generation of digital content. Against the backdrop of rapid advancements in AI technologies and the escalating demand for diverse and personalized digital content, the integration of API-based generative models emerges as a pivotal engine for progress in this domain. The findings of this research validate the significance of incorporating API-based generative AI models into a unified system, serving as a fundamental stride towards automating the process of digital content creation to meet contemporary market demands. Moreover, it underscores the potential of such integration in fostering the development of personalized and innovative solutions for end-users. The further effort of our research team will be aimed at the implementation of this concept and further exploration of its applicability across diverse domains.